(untitled) (International Journal of Engineering and Computer Science, 2014)
Wireless sensor network consists of spatially distributed autonomous sensors to monitor physical or environmental conditions such as temperature, sound, pressure etc. and cooperatively pass their data through the network to a main location. However, individual sensor nodes are vulnerable to some types of attacks because they are usually deployed in open and unprotected environments. Trust management, which models the trust on the behavior of the elements of the network, can be especially useful for a sensor network environment to enhance security. Various methods have been proposed for trust management in wireless sensor networks. A reactive hierarchical trust management scheme is proposed here which reduces the energy consumption rate of sensor nodes by calculating the trust values on demand.